2023
DOI: 10.1093/ofid/ofad241
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cardiometabolic Disease Risk Factors in People with HIV Initiating Anti-retroviral Therapy at a High-Volume HIV Clinic in Kampala, Uganda

Abstract: Background Cardiometabolic diseases are a leading cause of HIV-related morbidity and mortality, yet routine screening is not undertaken in high burden countries. We aimed to assess the prevalence and risk factors of the metabolic syndrome (MetS) and its components in adult Ugandan people living with HIV (PWH) initiating dolutegravir-based antiretroviral therapy (ART). Methods We conducted a cross-sectional study using baselin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
1
0
0
Order By: Relevance
“…Additionally, 29.4% had pre-hypertension, indicating a concerning trend, considering that the median age of this cohort of patients was only 33 years. Our findings support current research from the WHO African region which has shown substantially high rates of hypertension among both ART-naïve and -exposed PWH [20][21][22][23]. The findings of this study contribute to the limited literature on hypertension among PWH in Sierra Leone specifically and may provide valuable insights for HIV care providers and policymakers in designing appropriate interventions to address the growing burden of hypertension and CVDs in this vulnerable population.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, 29.4% had pre-hypertension, indicating a concerning trend, considering that the median age of this cohort of patients was only 33 years. Our findings support current research from the WHO African region which has shown substantially high rates of hypertension among both ART-naïve and -exposed PWH [20][21][22][23]. The findings of this study contribute to the limited literature on hypertension among PWH in Sierra Leone specifically and may provide valuable insights for HIV care providers and policymakers in designing appropriate interventions to address the growing burden of hypertension and CVDs in this vulnerable population.…”
Section: Discussionsupporting
confidence: 85%